2014
DOI: 10.1016/j.jbiomech.2014.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of 3D marker based scapular motion analysis: A systematic review

Abstract: Methods based on cutaneous markers are the most popular for the recording of three dimensional scapular motion analysis. Numerous methods have been evaluated, each showing different levels of accuracy and reliability. The aim of this review was to report the metrological properties of 3D scapular kinematic measurements using cutaneous markers and to make recommendations based on metrological evidence. A database search was conducted using relevant keywords and inclusion/exclusion criteria in 5 databases. 19 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 56 publications
(164 reference statements)
5
77
0
1
Order By: Relevance
“…Although substantial work has been done in validating the accuracy of non-invasive, skin-based measurement methods of tracking the scapula (Lempereur et al, 2014), errors due to skin movement are still prevalent, especially in shoulder elevation above 90° (Borstad and Ludewig 2002;Ludewig et al, 2004;Prinold et al, 2011;van Andel et al, 2009;Warner et al, 2012). It has been suggested that modifying marker design in combination with adhering to current recommendations regarding attachment location of skin-based marker clusters placed over the scapula could improve the accuracy of this measurement method (Lempereur et al, 2014). Furthermore, the accuracy of such measurements has chiefly been investigated in relation to shoulder and arm movement in mid-positions of the shoulder girdle, with no studies examining their accuracy in more complex movement of the shoulder girdle, such as end range clavicular protraction, retraction, elevation, and depression, which are commonly used during normal daily activities.…”
Section: Challenges In the Measurement Of Scapular Kinematicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although substantial work has been done in validating the accuracy of non-invasive, skin-based measurement methods of tracking the scapula (Lempereur et al, 2014), errors due to skin movement are still prevalent, especially in shoulder elevation above 90° (Borstad and Ludewig 2002;Ludewig et al, 2004;Prinold et al, 2011;van Andel et al, 2009;Warner et al, 2012). It has been suggested that modifying marker design in combination with adhering to current recommendations regarding attachment location of skin-based marker clusters placed over the scapula could improve the accuracy of this measurement method (Lempereur et al, 2014). Furthermore, the accuracy of such measurements has chiefly been investigated in relation to shoulder and arm movement in mid-positions of the shoulder girdle, with no studies examining their accuracy in more complex movement of the shoulder girdle, such as end range clavicular protraction, retraction, elevation, and depression, which are commonly used during normal daily activities.…”
Section: Challenges In the Measurement Of Scapular Kinematicsmentioning
confidence: 99%
“…Adequate spacing between markers allows a consistent capture of the markers by the cameras (Lempereur et al, 2014) and accuracy is increased when markers are further apart. This has led to the development of two types of AMC designs: A large base to which markers are directly attached (Warner et al, 2012) and a small base with markers mounted on pins (Lempereur et al, 2012;van Andel et al, 2009) (Figure 2.3).…”
Section: Acromion Marker Cluster (Amc) Designmentioning
confidence: 99%
See 3 more Smart Citations